2021
DOI: 10.1371/journal.pntd.0009354
|View full text |Cite
|
Sign up to set email alerts
|

Serious adverse reactions associated with ivermectin: A systematic pharmacovigilance study in sub-Saharan Africa and in the rest of the World

Abstract: Background Ivermectin is known to cause severe encephalopathies in subjects infected with loiasis, an endemic parasite in Sub-Saharan Africa (SSA). In addition, case reports have described ivermectin-related serious adverse drug reactions (sADRs) such as toxidermias, hepatic and renal disorders. The aim of this study was to identify suspected sADRs reported after ivermectin administration in VigiBase, the World Health Organization’s global individual case safety reports database and analyze their frequency rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 38 publications
(44 reference statements)
2
37
0
Order By: Relevance
“…Previous clinical trials and observational studies reported similar common AEs, including headache, pruritus, muscle pain, coughing, dyspnea, nausea, vomiting, diarrhea, confusion, and skin reactions [ 7 ]. The same events were reported in higher numbers through spontaneous reporting to the WHO’s Vigibase, although the incidence rate could not be quantified [ 17 ]. Safety studies conducted elsewhere using diverse study designs, target populations, and treatment indications reported varying incidence rates of mild-to-moderate AEs in the first two days of treatment [ 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous clinical trials and observational studies reported similar common AEs, including headache, pruritus, muscle pain, coughing, dyspnea, nausea, vomiting, diarrhea, confusion, and skin reactions [ 7 ]. The same events were reported in higher numbers through spontaneous reporting to the WHO’s Vigibase, although the incidence rate could not be quantified [ 17 ]. Safety studies conducted elsewhere using diverse study designs, target populations, and treatment indications reported varying incidence rates of mild-to-moderate AEs in the first two days of treatment [ 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although millions of people in Africa are receiving periodic MDA, safety data from large-scale active CEM studies are scarce partly due to the lack of fully functional pharmacovigilance systems in the region [ 10 , 11 , 12 ]. The WHO’s global individual case safety reports database (VigiBase) recently reported serious suspected ADRs and safety signals associated with ivermectin use and the under-reporting of ADRs in SSA [ 17 ]. Under or incomplete reporting of AEs, lack of information on baseline characteristics embracing the number of drug administrations, and the absence of denominators are major drawbacks inherent in spontaneous reporting pharmacovigilance databases such as VigiBase [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Precautions and Adverse neuropsychiatric Effects: The common neuropsychiatric adverse effects (A/Es) (data from the treatment of helminthic infections) are weakness, increased sleep, headache (10%), dizziness (7.5%)( Chandler, 2018 ). Additionally, encephalopathies/delirium, psychotic disorders( Mohapatra & Sahoo, 2015 ), suicidal behavior ( Kaur et al, 2017 ) have been reported with its use( Campillo et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Disproportionality analysis revealed a significant association between systemic ivermectin and reporting of any SCARs, confirming a recent study of VigiBase, another pharmacovigilance database. 11 Interestingly, SCARs were reported more in African countries compared to other cutaneous AEs. This could be explained by under‐reporting of milder cutaneous AEs in these countries compared with North American or European countries, or by increased incidence of HIV carriers in Africa, 12 which is a risk factor for some SCARs, in particular SJS and TEN.…”
Section: Discussionmentioning
confidence: 99%